Relationship between undergraduates’ University-Library Usage for Academic Purpose and their Academic Performance in Sri Lankan Universities - Karannagoda, Neluka Maduranga (University of Colombo, 2022)
Most of the Sri Lankan government university libraries are maintained in a complicated and broad space incurring a great expense with the assistance of a big carder. Though the situation is this, the present-day undergraduates do not effectively use the university library for their education, and they tend to extract information from untrusted information sources. As public funds maintain these libraries, library authorities are responsible for demonstrating their value, contribution and effectiveness for the academic success of the undergraduates since the main requirement of maintaining university libraries is to support undergraduates’ academic success. Therefore, this research study focuses on finding a relationship between undergraduates’ university library usage for academic purpose (AP) and their Academic Performance (APE) in Government Universities in Sri Lanka. This research is basically quantitative in nature and has employed the survey method. Further the research philosophy is positivism and research approach is deductive. When collecting the data, undergraduates of three academic years, two universities, five faculties and eight library usage types were used. Time horizon for this research study is cross sectional. According to the findings, this study concluded that there is a significant weak positive relationship between the undergraduates’ UL usage and their APE for all undergraduates. But this relationship varies when the gender, faculty and the library usage types are considered separately. When it is considered the faculty wise relationship, Undergraduates’ of Faculty of Management and Education demonstrate a strong positive relationship between UL usage and APE while Faculty of Arts demonstrates a weak positive relationship. However, for Faculty of Science and Law there is no significant positive relationship between undergraduates’ UL usage and their APE. Finally, this study proved that there is a significant difference between the GPAs of the UL users and UL non-users for AP. This is one of the first attempts to find a relationship between undergraduates’ university library usage for educational activities and their APE by using three academic years, five faculties, two universities and eight library usage types.
Keywords: Academic performance; Academic purpose; Undergraduates; University library usage